2022
DOI: 10.3390/nu14193971
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Visceral Fat Area Measured by Bioelectrical Impedance Analysis on Clinical and Oncologic Outcomes of Colorectal Cancer

Abstract: Background: Some studies have shown that an increase in visceral fat is associated with postoperative clinical and oncologic outcomes. However, no studies have used bioelectrical impedance analysis (BIA) to determine the effects of visceral fat on the oncologic outcomes of colorectal cancer (CRC). This study aimed to investigate the impact of preoperative visceral fat area measured by bioelectrical impedance analysis on clinical and oncologic outcomes of colorectal cancer Methods: This study included 203 patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The utilization of bioelectrical impedance analysis (BIA) for measuring body composition has generated significant interest in using various indicators, including skeletal muscle index (SMI), phase angle (PA), fat mass (FM), fat-free mass (FFM), fat-free mass index (FFMI), cellular water, to predict outcomes in patients with lung cancer ( 3 , 4 ), breast cancer ( 5 ), prostate cancer ( 6 ), gastric cancer ( 7 ) and colorectal cancer ( 8 ). In contrast to traditional BIA methods, bioelectrical impedance vector analysis BIVA can provide more objective information about hy and BCM ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of bioelectrical impedance analysis (BIA) for measuring body composition has generated significant interest in using various indicators, including skeletal muscle index (SMI), phase angle (PA), fat mass (FM), fat-free mass (FFM), fat-free mass index (FFMI), cellular water, to predict outcomes in patients with lung cancer ( 3 , 4 ), breast cancer ( 5 ), prostate cancer ( 6 ), gastric cancer ( 7 ) and colorectal cancer ( 8 ). In contrast to traditional BIA methods, bioelectrical impedance vector analysis BIVA can provide more objective information about hy and BCM ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [ 30 ] reported that body composition indices, including fat and muscle indices, were related to platelet and lymphocyte ratios in CRC, particularly in male patients. Previous research has indicated that preoperative VFA measured using the BIA could serve as an independent prognostic factor for DFS [ 15 31 ]. However, in our study, no significant associations were observed between sarcopenia, VFA, phase angle, and PIV.…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a well-known noninvasive anthropometric measurement including body composition, fat index, muscle index, obesity index, and phase angle [ 15 ]. And skeletal muscle index (SMI) was calculated to diagnose sarcopenia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have evaluated postoperative changes in body composition using BIA and analyzed the risk factors for postoperative complications in patients with gastric cancer [21][22][23]. Moreover, in patients with colorectal cancer, a preoperative low SMI based on the BIA method was considered a risk factor for postoperative ileus [24], and preoperative visceral fat area measured by BIA was an independent prognostic factor for disease-free survival [25]. Only a few studies have investigated the relationship between the prognosis after radical resection of PDAC and body composition changes assessed by BIA.…”
Section: Discussionmentioning
confidence: 99%